Solutions of Nonlinear Integro-Partial Differential Equations by the Method of G′/G,1/G - Daba Meshesha Gusu; Chala Bulo (Advances in Mathematical Physics)
In this article, a special expansion method is implemented in solving nonlinear integro-partial differential equations of 2+1-dimensional using a special expansion method of G′/G,1/G. We obtained the solutions for 2+1-dimensional nonlinear integro-differential equations in real physical phenomena. The method is applied on 2+1-dimensional space time and solved in three different cases: hyperbolic, trigonometric, and rational functions. The obtained solutions for each result were illustrated by graphical plots using Wolfram Mathematica 9.0 software packages. Furthermore, the obtained results are exactly fit with exact solutions which solves the complicity of finding the solution for nonlinear integro-partial differential equations. Finally, the method is powerful and effective to solve partial differential equations of nonlinear integro form.